TINGKAT RESPON ORANGTUA TERHADAP PENGGUNAAN GRUP WHATSAPP DALAM PROGRAM PARENTING DI PAUD SEULANGA MEULIGO ACEH SELATAN - Fitriani, Dewi; Fajriah, Heliati; Shovianda, Erika (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
Involving parents in a continuous learning process from school and home is a challenging program for an educational institution. The classic problem most often encountered is the absence of parents from parenting program activities organized by schools. The presence of a parenting program which is able to connect or bring parents together is indeed needed in supporting the harmony of the learning process. This study aims to determine the response of parents to the implementation of the parenting design program using the WhatsApp group. This study uses a quantitative approach research design with data collection techniques carried out by distributing questionnaires in the form of a Guttman scale which are then validated with the help of SPSS and measured by a percentage index. Research data obtained from 30 respondents from total 120 population. The results showed 87.99% of respondents showed a positive response to the application of group WhatsApp in parenting activities at school.